User influence on mobile terminal antennas: a review of challenges and potential solution for 5G antennas - Khan, Rizwan; Al-Hadi, Azremi Abdullah; Soh, Ping; Kamarudin, Muhammad Ramlee (IEEE, 2018)
This paper presents a comprehensive review of mobile terminal antenna researches performed in the past seven years and the current challenges related to the user’s influence on the performance of fifth generation (5G) terminal antennas. The main challenges for the designing of mobile terminal antennas are to meet the compact size requirements of built-in structures and their multiband capabilities. The antenna design techniques that are used to achieve broader operating bandwidths with smaller antenna dimensions will be first discussed. This is followed by the effects of user interactions with the head/hand for mobile antennas in terms of radiation efficiency and, consequently, the correlation of multiple input multiple output (MIMO) antenna systems. The ultimate aims of this paper are as follows: 1) to highlight the different frequencies of mobile terminal antennas for different applications; 2) to highlight mobile terminal antennas that have been developed for 5G application; 3) to study and discuss the effects of user’s hand on 5G mobile terminal antennas; and 4) to discuss the research gap, issues, and challenges in the field of user’s effects on mobile terminal antennas for 5G applications. In addition to that, an investigation of the users’ hand effects on two MIMO mobile terminal antennas operational in the sub-6-GHz 5G band is presented. This investigation performed using two MIMO antennas is an attempt to formulate guidelines on efficient mobile terminal antenna design in the presence of user’s hand in C Band (from 3.4 to 3.6 GHz) and LTE-U Band 46 (from 5.15 to 5.925 GHz).
Keywords: Electromagnetic influence of users; mobile terminal antennas; multiband antennas; MIMO antennas